Environmental chemical exposures in the urine of dogs and people sharing the same households. Issue 1 (2nd October 2020) - Craun, Kaitlyn; Luethcke, Kristofer Ross; Shafer, Martin; Stanton, Noel; Zhang, Chen; Schauer, James; Faulkes, Joshua; Sundling, Kaitlin E.; Kurtycz, Daniel; Malecki, Kristen; Trepanier, Lauren
Abstract: Introduction: Urothelial carcinoma (UCC) develops in both humans and dogs and tracks to regions of high industrial activity. We hypothesize that dogs with UCC may act as sentinels for human urothelial carcinogen exposures. The aim of this pilot study was to determine whether healthy people and dogs in the same households share urinary exposures to potentially mutagenic chemical carcinogens. Methods: We measured urinary concentrations of acrolein (as its metabolite 3-HPMA), arsenic species, 4-aminobiphenyl, and 4-chlorophenol (a metabolite of the phenoxyherbicide 2, 4-D) in healthy dogs and their owners. We assessed possible chemical sources through questionnaires and screened for urothelial DNA damage using the micronucleus assay. Results: Biomarkers of urinary exposure to acrolein, arsenic, and 4-chlorophenol were found in the urine of 42 pet dogs and 42 owners, with 4-aminobiphenyl detected sporadically. Creatinine-adjusted urinary chemical concentrations were significantly higher, by 2.8- to 6.2-fold, in dogs compared to humans. Correlations were found for 3-HPMA ( r = 0.32, P = 0.04) and monomethylarsonic acid ( r = 0.37, P = 0.02) between people and their dogs. Voided urothelial cell yields were inadequate to quantify DNA damage, and questionnaires did not reveal significant associations with urinary chemical concentrations. Conclusions: Healthy humans and pet dogs have shared urinary exposures to known mutagenic chemicals, with significantly higher levels in dogs. Higher urinary exposures to acrolein and arsenic in dogs correlate to higher exposures in their owners. Follow-up studies will assess the mutagenic potential of these levels in vitro and measure these biomarkers in owners of dogs with UCC.